ANALISA KETERAMPILAN MANAJERIAL KEPALA SEKOLAH PADA PENINGKATAN DISIPLIN SISWA DI SMA NEGERI 1 KOTA JAMBI - Septiany, Dwi; Andriani, Lili (SJEE (Scientific Journals of Economic Education), 2022)
Improving the quality of education is largely determined by the ability of the principal in empowering teaching staff and members of the community as a whole. The role of the principal, among others, is to develop so that schools become good educational institutions and are able to achieve educational goals. In this study, the principal's managerial skills are needed to increase the existing resources in the school, both physical resources and non-physical resources. The process of improving the quality of education in schools must pay attention to all components in schools such as educators and education staff, including the facilities and infrastructure in it. Keywords: Managerial Skills, Discipline Improvement